2019
DOI: 10.1016/j.omto.2019.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal Leucine-Rich-Alpha2-Glycoprotein 1 Derived from Non-Small-Cell Lung Cancer Cells Promotes Angiogenesis via TGF-β Signal Pathway

Abstract: Non-small-cell lung cancer (NSCLC) is a major cause for cancer-related deaths around the globe, partially due to the frequent recurrence and metastasis. Leucine-rich-alpha2-glycoprotein 1 (LRG1) is reportedly upregulated in several cancers including NSCLC; however, its functions in NSCLC remain elusive. We used quantitative real-time PCR and western blot assays to evaluate the expression patterns of LRG1 in tumor tissues collected from NSCLC patients, as well as NSCLC cell lines, and examined the effects of LR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 25 publications
2
32
0
Order By: Relevance
“…Our previous work demonstrated that LRG1 significantly accelerated diabetic kidney injury and TGF-β/ALK1-induced angiogenesis in an experimental model of early diabetic kidney disease [6]. Consistently, LRG1 promotes angiogenesis by modulating endothelial TGF-β signaling in retinal vascular [5] and NSCLC [22]. LRG1 can also modulate the invasion and migration of glioma cell lines through the TGF-β signaling pathway [23].…”
Section: Discussionmentioning
confidence: 79%
“…Our previous work demonstrated that LRG1 significantly accelerated diabetic kidney injury and TGF-β/ALK1-induced angiogenesis in an experimental model of early diabetic kidney disease [6]. Consistently, LRG1 promotes angiogenesis by modulating endothelial TGF-β signaling in retinal vascular [5] and NSCLC [22]. LRG1 can also modulate the invasion and migration of glioma cell lines through the TGF-β signaling pathway [23].…”
Section: Discussionmentioning
confidence: 79%
“…The importance of exosomes in governing various physiological and pathological conditions is no longer in doubt. Exosomes may transfer signals to induce EMT, cell migration and invasion, angiogenesis, and metastasis processes [ 5 , 8 , 9 , 10 , 11 ]. It should be noted that the majority of studies were performed with exosomes from cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…These vesicular structures are highly stable and are small enough to penetrate into and interact with different tissues. Exosomes are involved in key physiological processes such as cell-to-cell communications [3], proliferation [4], migration [5], invasion [6], angiogenesis [7], and tumor growth [8] through the horizontal transfer of RNA and proteins.…”
Section: Introductionmentioning
confidence: 99%